Optimized designing of PID controller for variable speed wind turbine systems using PSO algorithm - Abdolzadeh, Somayeh; Mohammadi, Seyed Mohammad Ali (Ciência e Natura, 2015)
The PID controller design is a very popular method for controlling industrial processes and due to its simple structure and effective operation; it is used in a wide range of industries. In this paper, a method is provided for setting up the PID controller and Particle swarm optimization (PSO) algorithm is used to design a variable speed wind turbine system. The provided method has advantages such as easy implementation, stable convergence characteristics and high performance in computing. Finally the results are displayed.